Хералдичкиот лав на марки - Heraldic Lion on Post Stamps - Simjon Simev (Македонски хералд - Macedonian Herald, 2019)
Heraldry as a science of the coats of arms and philately - a collector’s love of collecting sand studying stamps: they are inseparable. The artistic expression brings them closer.This is confirmed by the postage stamps issued by the Republic of Macedonia. Specifically: PE Macedonian Post, under the heading Heraldry of Macedonia issued postal stationery with face value of 10; 36 and 9; 36 denars; including First Day Envelope. The postage stamps were printed on 19 June 2002 and 23 June 2003. The motif of the heraldic lion on the stamps was taken from various armorials.